Magmatic history and parental melt composition of olivine‐phyric shergottite LAR 06319: Importance of magmatic degassing and olivine antecrysts in Martian magmatism. (18th June 2013) - Balta, J. Brian; Sanborn, Matthew; McSween, Harry Y.; Wadhwa, Meenakshi
Abstract Several olivine‐phyric shergottites contain enough olivine that they could conceivably represent the products of closed‐system crystallization of primary melts derived from partial melting of the Martian mantle. Larkman Nunatak (LAR) 06319 has been suggested to represent a close approach to a Martian primary liquid composition based on approximate equilibrium between its olivine and groundmass. To better understand the olivine–melt relationship and the evolution of this meteorite, we report the results of new petrographic and chemical analyses. We find that olivine megacryst cores are generally not in equilibrium with the groundmass, but rather have been homogenized by diffusion to Mg# 72. We have identified two unique grain types: an olivine glomerocryst and an olivine grain preserving a primary magmatic boundary that constrains the time scale of eruption to be on the order of hours. We also report the presence of trace oxide phases and phosphate compositions that suggest that the melt contained approximately 1.1% H2O and lost volatiles during cooling, also associated with an increase in oxygen fugacity upon degassing. We additionally report in situ rare earth element measurements of the various mineral phases in LAR 06319. Based on these reported trace element abundances, we estimate the oxygen fugacity in the LAR 06319 parent melt early in its crystallization sequence (i.e., at the time of crystallization of the low‐Ca and high‐Ca pyroxenes), the rare earth element composition of the parent melt, and those of melts in equilibrium with later formed phases. We suggest that LAR 06319 represents the product of closed‐system crystallization within a shallow magma chamber, with additional olivine accumulated from a cumulate pile. We infer that the olivine megacrysts are antecrysts, derived from a single magma chamber, but not directly related to the host magma, and suggest that mixing of antecrysts within magma chambers may be a common process in Martian magmatic systems.